Эндаумент как инновационный механизм финансирования автономных социально-культурных учреждений в современных (Путеводитель предпринимателя, 2020)
In given article along with off-budget sources of welfare sphere establishments financing there is such a long-term source of financing as the endowment-fund which is intended for financial support of establishment (organisation), aimed at the reception of income from the investment.